Ultrasound‐Induced Nitric Oxide‐Propelled Nanomotor for Multimodal Theranostics of Cancer with Deep Penetration and Extended Lifetime - Xue Xu; Jinxu Cao; Yan Mu; Hao Zhang; Ya‐Lei Wang; Mengzhen Chen; Yuce Li; Qian Hua (Advanced Science)
Abstract Cancer treatment is often ineffective due to poor bioimaging and resistance to standard therapies. This issue is exacerbated by multiple low‐penetrable bio‐barriers that limit the theranostic agents’ effectiveness in tumors. Here, a hollow nanomotor PM‐HMSN/Arg is fabricated by a sequential process involving: electrostatic adsorption of Mn2+, loading of l‐Arg, and coating of platelet membrane (PM), respectively. This nanomotor uses l‐Arg as an NO donor and ultrasound (US) as a trigger for NO release. After administration, it improves tumor penetration via a “tethering‐relaxing‐drilling” mechanism, overcoming bio‐barriers during delivery from blood vessels to tumor cells. NO regulates the metabolism of tumor vascular endothelial cells, facilitating relaxation, and enhances cytotoxicity by participating in reactive oxygen species metabolism. More importantly, the nanomotor's active motion enhances tissue penetration and retention in cancer, increasing therapeutic effects. In addition, continuous in situ NO generation extends US imaging signal lifetime. This innovative nanomotor shows promise for multimodal theranostics in low‐penetrable tumors.